2015
DOI: 10.1111/jop.12381
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA hypomethylation is associated with the development and poor prognosis of tongue squamous cell carcinoma

Abstract: Global hypomethylation was an independent biomarker for the development and poor prognosis of TSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…This is in accordance with results from an earlier small-scale study that also found no prognostic value for 5mC immunoreactivity in PC ( n = 48) [ 39 ]. In contrast, global loss of 5mC has been associated with poor prognosis in tongue squamous cell carcinoma [ 45 ], while increased 5mC levels in myelodysplastic syndrome have been linked with a worse prognosis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with results from an earlier small-scale study that also found no prognostic value for 5mC immunoreactivity in PC ( n = 48) [ 39 ]. In contrast, global loss of 5mC has been associated with poor prognosis in tongue squamous cell carcinoma [ 45 ], while increased 5mC levels in myelodysplastic syndrome have been linked with a worse prognosis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detailed procedures of tissue microarray (TMA) construction were described in our previous study [ 15 ]. The TMA block consisted of 129 cores, including 43 trios with each trio containing 2 cores from the tumor tissue and 1 core from the non-cancerous epithelium of the same patient.…”
Section: Methodsmentioning
confidence: 99%
“…TMA blocks were cut into 4-μm paraffin sections, dewaxed in xylene, rehydrated through a series of graded alcohols, and subsequently washed for 5 minutes with phosphate-buffered saline (PBS) [ 50 ]. The Novolink max polymer detection system (Leica, Newcastle Upon Tyne, United Kingdom) was used for the following immunostaining processes.…”
Section: Methodsmentioning
confidence: 99%